Bringing Self-Kindness Into the Workplace: Exploring the Mediating Role of Self-Compassion in the Associations Between Attachment and Organizational Outcomes - Reizer, Abira (Frontiers in Psychology, 2019)
Research has shown that individual differences in adult attachment predict several organizational outcomes. However, little is known about the mechanism that underlies these associations. The current study examines whether self-compassion can serve as a potential mediator explaining the associations between individual differences in attachment and organizational outcomes. Four outcome measures were evaluated: job performance (HPQ; Kessler et al., 2003), OCB (Goodman and Svyantek, 1999), turnover intentions (Abrams et al., 1998), and emotional exhaustion (Schaufeli et al., 1996). In addition, participants (N = 202, response rate 81%) also completed several questionnaires assessing attachment style (ECR; Brennan et al., 1998) and self-compassion (SCS; Neff, 2003). Using structural equation modeling (SEM) for testing the research hypotheses, the hypothesized model was supported, with self-compassion mediating the relationship between attachment styles and all four work-related outcomes. The research findings suggest that self-compassion can provide a solid mechanism for understanding organizational outcomes and for understanding individual differences related to attachment functioning in the workplace.